2022
DOI: 10.1038/s41378-022-00376-0
|View full text |Cite
|
Sign up to set email alerts
|

Advanced tools and methods for single-cell surgery

Abstract: Highly precise micromanipulation tools that can manipulate and interrogate cell organelles and components must be developed to support the rapid development of new cell-based medical therapies, thereby facilitating in-depth understanding of cell dynamics, cell component functions, and disease mechanisms. This paper presents a literature review on micro/nanomanipulation tools and their control methods for single-cell surgery. Micromanipulation methods specifically based on laser, microneedle, and untethered mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 183 publications
(199 reference statements)
0
19
0
Order By: Relevance
“…Procedures such as percutaneous transcatheter cardiac surgeries and targeted drug deliveries in clinical medicine are showing advantages of producing more effectiveness and less complications. In basic medical research, several methods of single-cell manipulation have been developed which have shown remarkable potential in understanding and investigating cellular processes at the most minuscule level ( Shakoor et al, 2022 ). Widely-used single-cell manipulation techniques include glass microneedles, which are glass capillaries that come in a variety of sizes, robotically or manually controlled, microfluidics, which are controlled microchannel networks that perform cellular and molecular experiments, magnetic tweezers, which perform operations on cells using magnetic field-controlled microrobots, and optical tweezers, which employ forces exerted by light to manipulate cells ( Shakoor et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Procedures such as percutaneous transcatheter cardiac surgeries and targeted drug deliveries in clinical medicine are showing advantages of producing more effectiveness and less complications. In basic medical research, several methods of single-cell manipulation have been developed which have shown remarkable potential in understanding and investigating cellular processes at the most minuscule level ( Shakoor et al, 2022 ). Widely-used single-cell manipulation techniques include glass microneedles, which are glass capillaries that come in a variety of sizes, robotically or manually controlled, microfluidics, which are controlled microchannel networks that perform cellular and molecular experiments, magnetic tweezers, which perform operations on cells using magnetic field-controlled microrobots, and optical tweezers, which employ forces exerted by light to manipulate cells ( Shakoor et al, 2022 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Optical tweezers have been widely used in cell surgery to position cells precisely for the insertion of glass capillaries. [2][3][4] Magnetic fields have also been used to rotate cells modified with magnetic particles. [5][6][7] Rotational motion of cells is induced by convective hydrodynamic forces generated by acoustic waves in microfluidic channels.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of nanoprobe technologies (37,38) presents a unique opportunity to study mtDNA heteroplasmy with a su cient sampling resolution, simultaneously preserving the spatial information needed to study somatic mtDNA variation and clonal expansion. A range of micro-and nanoprobe-based technologies have been recently developed to enable the localized probing of cells and tissue (39,40,41,42,43).…”
Section: Introductionmentioning
confidence: 99%